Analisis Determinan Pertumbuhan Ekonomi Wilayah Eks Karesidenan Surakarta Tahun 2011-2015 - PANGESTU, INDRIAWATI, Drs. Yuni Prihadi Utomo, M.M (2017)
This research aims to analyze the investment, labor, and human capital investment against economic growth in Ex-Karesidenan Surakarta year 2011- 2015. This type of research is a composite time series (in order of time) and cross section. Types of data used are secondary data with panel data type. The sample in this research is 35 observation. The most appropriate model selected in this research is the Random Effect Method (REM). REM models have power high enough. Based on the test results of F, simultaneous variable investment, labor, human capital investment effect on the economic growth in the Ex-Karesidenan Surakarta year 2011-2015. Determinant of the coefficients of test results (R2) showed that the magnitude of R-square value is 0,764721, or of 76,47%. This means that the variation of the economic growth can be explained by the independent variable that is in statistical models such as investment, labor, and human capital investment . While the rest of 23,53% explained by other factors that are not included in the model. Based on a test of the validity of the influence (t-test) on significance (α) of 0.05, labor and human capital investment have influence positif significantly to the economic growth, while the investment variable has no influence on the economic growth in the regional Eks- Karesidenan Surakarta in year 2011-2015.